2022
DOI: 10.1017/s1047951122000907
|View full text |Cite|
|
Sign up to set email alerts
|

“The only thing I wonder is when I will have surgery again”: everyday life for children with right ventricle outflow tract anomalies during assessment for heart surgery

Abstract: Many children with complex right ventricle outflow tract anomalies such as Tetralogy of Fallot, common arterial trunk, and pulmonary atresia with ventricular septal defect require repeated heart surgeries early in life, but also later throughout their lifetime, thereby emphasising the importance of careful life-long follow-up. The need for repeated heart surgeries during childhood is recognised as a heavy burden on the child. Optimising the time point for re-intervention is important, since delaying re-interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the present study, six month after surgery, the parents experienced relief and strength with traces of adaptation. We have earlier shown that their children adapted to managing their heart disease in their everyday life and could cope with the knowledge that future heart surgeries were likely [9]. An adaptation and development of strategies for managing the child's CHD is shown to be essential to coping for parents too [3], and this adaptation process may affect their need for support which could be valuable information for the health care providers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, six month after surgery, the parents experienced relief and strength with traces of adaptation. We have earlier shown that their children adapted to managing their heart disease in their everyday life and could cope with the knowledge that future heart surgeries were likely [9]. An adaptation and development of strategies for managing the child's CHD is shown to be essential to coping for parents too [3], and this adaptation process may affect their need for support which could be valuable information for the health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…This need for repeated operations, that the child will never be free of the fear of surgery, is a challenge for the parents. This challenge may have contributed to an adaptation process, perhaps facilitated by their child's inner strength and well-being thus far [9]. They had adapted to and developed strategies for suppressing their worries and anxiety until the more critical situations, especially when a reoperation become a reality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation